The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/5895439
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Dependent Protective Effect of Selenium against UVA Irradiation in Primary Human Keratinocytes and the Associated DNA Repair Signature

Abstract: Few studies have focused on the protective role of selenium (Se) against skin aging and photoaging even though selenoproteins are essential for keratinocyte function and skin development. To the best of our knowledge, the impact of Se supplementation on skin cells from elderly and young donors has not been reported. Therefore, the main objective of our study was to evaluate the effects of Se supplementation on skin keratinocytes at baseline and after exposure to ultraviolet A (UVA) irradiation. Low doses of Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
(54 reference statements)
0
18
0
1
Order By: Relevance
“…Consequently, the treatment was not interrupted by any of the study participants. The methods used to evaluate product tolerability have been previously validated in relevant studies [51][52][53]. Apart from the two adverse events previously mentioned, all the investigated aspects concerning the product were positively assessed by enrolled subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the treatment was not interrupted by any of the study participants. The methods used to evaluate product tolerability have been previously validated in relevant studies [51][52][53]. Apart from the two adverse events previously mentioned, all the investigated aspects concerning the product were positively assessed by enrolled subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A novel oral nutritional (dietary) supplement based on Pinus pinaster bark extract and proanthocyanidin-rich grape seed extract, has been developed to be incorporated in the armamentarium for the treatment of melasma. Vitamin E and C, selenium and nicotinamide have also been shown to reduce the negative effects of UV radiation on skin by eliminating reactive oxygen species and reducing the erythema associated with UV [18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed in a study by Jobeili et al, which showed that selenium delays skin ageing by protecting keratinocyte stem cells [ 91 ]. Favrot et al showed that low doses of Se (30 nM) provide potent protection against UVA-induced cytotoxicity in young keratinocytes (from 20–30-year-old donors), while higher concentrations (240 nM) were required for protective efficacy in old keratinocytes (from donors 60–70 years old) [ 92 ].…”
Section: Selected Substances Of Importance For Skin Functionmentioning
confidence: 99%
“…Selenium supplementation is an important strategy for inhibiting wrinkles, because it can reverse ultraviolet light damage and play an anti-ageing role in the skin [ 89 , 92 ]. Kim et al showed that a selenium-rich tuna heart extract enhanced collagen synthesis and promoted the proliferation of skin fibroblasts, thus having anti-ageing and anti-wrinkle effects [ 93 ].…”
Section: Selected Substances Of Importance For Skin Functionmentioning
confidence: 99%